Soilsurface temperatures in 2 cm depth between summer 2018 and 2019 with iButton-sensor 211 in the North Slope of Alaska, USA - Langer, Moritz; Kaiser, Soraya; Stuenzi, Simone Maria; Schneider von Deimling, Thomas; Oehme, Alexander; Jacobi, Stephan (In: Langer, M et al. (2020): Soilsurface temperatures in 2 cm depth between summer 2018 and 2019 with iButton-sensors in the North Slope of Alaska (USA), around Churchill (Canada) and the region of Illirney and Lena-Viluy (Russia) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.914327, 2020)
Soil surface temperatures were collected with help of iButtons along different transects and clusters in the North Slope of Alaska. The interval was set to 4 hours resp. 4.25 hours. Different models of iButtons were used (with a resolution of 0.0625 °C and 0.5°C resp.), see Comment.
Keywords: ibuttons; soil surface temperature